Case Report: Elective Circumcision in a 10-Year-Old Boy with a Review of Conventional and Modern Methods - Muhammad Irsa Madjid; Izza Mumtazati (The International Journal of Medical Science and Health Research, 2025)
Introduction: Male circumcision is a longstanding procedure performed worldwide for cultural, religious, and medical reasons. In Indonesia, it is commonly carried out on children aged 5–12 years, typically using the dorsal slit technique. Objective: This report aims to present a case of a 10-year-old male circumcised for religious reasons and to compare conventional and modern circumcision techniques. Case Report: A 10-year-old boy, accompanied by his parents, presented for circumcision due to religious reasons. The patient was asymptomatic, with a fully retractable foreskin and no anatomical abnormalities. A dorsal slit circumcision was performed under local anesthesia, resulting in an uneventful recovery and proper wound healing. Discussion: Evidence suggests that circumcision can reduce the risk of STIs, including HIV, HPV, and HSV, by limiting pathogen entry and altering the local immune environment. Modern techniques, such as clamp-assisted and adhesive methods, have shown advantages over conventional methods, including shorter operative times, fewer complications, and improved cosmetic outcomes. Conclusion: Male circumcision remains a valuable public health measure with significant cultural and medical benefits. Adoption of modern techniques may further enhance patient outcomes while preserving the traditional advantages of the procedure.